Manejo del síndrome de transfusión feto fetal en pandemia COVID-19: reporte de caso - Rojas, Ramiro (2023)
The twin-to-twin transfusion syndrome (TTTS) is a potentially lethal complicationthat can occur in monochorionic twin pregnancies due to an imbalance in placentalblood flow. Diagnosis is based on amniotic fluid discordance and classifiedusing the Quintero staging system. The primary treatment is fetoscopic laserphotocoagulation (FLP) of placental anastomoses. A successful case of FLP treatmentin a monochorionic diamniotic twin pregnancy with TTTS during COVID-19 pandemicin Peru is presented.